The pillars of economic diversification in Saudi Arabia. (2018) - Euchi, Jalel; Omri, Anis; Al-Tit, Ahmad
The success of economic diversification constitutes a key factor for sustainable economic growth. Therefore, a country that its economy only based on income from natural resources is in danger of instability. In addition, this diversification creates jobs, reduces poverty and improves the life and institution's qualities. After the first boom in 1970, the Saudi Arabia government has established 11 development plans, each one covering five years and their main objective is how to build a diversified economy. Accordingly, this paper aims to analyse the strategies of economic diversification in Saudi Arabia based on four variables: investment in education, entrepreneurship, international tourism and oil production over the period 1970-2014. Using the FMOLS technique, we found that oil production has the highest contribution to economic growth in Saudi Arabia, followed by the tourism sector and entrepreneurship activity, while, the contribution of education is positive, but insignificant. Research and policy recommendations are also discussed.